OKE STAR: Supporting the success of lesson study in high school - Hayuana, Wachidah; Chotimah, Husnul; Ibrohim, Ibrohim; Susilo, Herawati; Damopolii, Insar; Susanti, Eni; Sasea, Louis Ivana; Syahriridani, Muh. (Journal of Research in Instructional, 2024)
The first aim of our study is to document how the SBLS implementation process works. The second aim is to analyze teacher and student responses to implementing a School Based Lesson Study (SBLS). This research is survey research. The survey was conducted at one of the state high schools in Malang. The data collection process was carried out through observation, interviews, and the administration of questionnaires. Data collection was carried out in May 2024. Participants in this study were 33 students. They are 1 school principal, three Indonesian language subject teachers, and 29 class XI science students. A total of 16 male students and 13 female students. The students' ages range from 15 to 16 years. Observation, interviews, and student and teacher response questionnaires collected data. Data was analyzed qualitatively and quantitatively. The survey results show that implementing Lesson Study (LS) in schools has gone well. Students no longer look awkward when observed; teachers are skilled at planning and reflecting on learning outcomes. The school principal actively participates in LS activities by implementing the OKE STAR method. The response of teachers and students to learning that uses LS activities is very good.